Implementation of Inclusion-Based PAI Learning to Learning Disability Students in Class III SD UNP Laboratory Development - Sekarayu, Acacia Ita; Satria, Rengga (Darul Yasin Al Sys, 2023)
Islamic Religious Education for children with special needs is of course very necessary so that they can carry out religious law and fear Allah SWT. Teaching Islamic religious education to students with special needs has difficult challenges and is full of challenges. Because teachers must also be required to be able to combine inclusive classroom conditions with normal students. Besides that, efforts to achieve efficiency and effectiveness in achieving the goals of Islamic Religious Education certainly also need the right learning strategy. This study aims to determine the learning strategies used by PAI teachers in dealing with Learning Disability students in class III SD Pembangunan Laboratorium UNP. The research method used uses qualitative methods with descriptive qualitative research types. Data collection techniques using the method of observation, interviews, and documentation. The results of this study are that in SD Pembangunan Laboratorium UNP in class III still uses the 2013 curriculum. In teaching PAI teachers adjust learning methods to the needs of students by using the lecture and question and answer method. According to PAI teachers, this is because their only obstacle is learning, not listening. Besides that, PAI teachers prioritize service aspects in implementing PAI learning such as talking to children, providing meaningful experiences, and having adaptive behavior with Learning Disability students.